Analisis Dampak Cloud Computing terhadap Keamanan Sistem dan Data - Razman Rifany; Mario Dwi Prakoso; Pandu Dwi Laksono (Prosiding Seminar Nasional Teknoka, 2023)
This research focuses on the impact of cloud computing. The research methodology involves systematicliterature review, case studies, data analysis, and theoretical examination to collect supportive data andreferences, aiming to maximize research efficiency. The study also incorporates mitigation strategies andrisk management approaches. The findings indicate that the impact of cloud computing on system securityand data integrity can be tangibly measured through cloud resource testing. Utilizing comprehensiveanalytical methods sheds light on security vulnerabilities that may arise during cloud computing adoption.The research identifies key challenges faced by cloud users, such as unauthorized access and data leakage.Survey outcomes and cloud resource testing reinforce the necessity for focused security policy development,emphasizing the implementation of best practices. Data security measures recommended includeauthentication methods, encryption techniques, and selecting trustworthy cloud services. These securitysteps serve as safeguards to enhance data protection within the cloud environment.